2006
DOI: 10.1111/j.1468-1293.2006.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of risk factors for cardiovascular disease in HIV‐infected patients over time: the Swiss HIV Cohort Study

Abstract: Objective Metabolic changes caused by antiretroviral therapy (ART) may increase the risk of coronary heart disease (CHD). We evaluated changes in the prevalence of cardiovascular risk factors (CVRFs) and 10‐year risk of CHD in a large cohort of HIV‐infected individuals. Methods All individuals from the Swiss HIV Cohort Study (SHCS) who completed at least one CVRF questionnaire and for whom laboratory data were available for the period February 2000 to February 2006 were included in the analysis. The presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
5
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 20 publications
(16 reference statements)
6
90
5
5
Order By: Relevance
“…Such conditions affected 13-48% of our subjects, rates similar to those published from other studies of HIV-infected patients. 3,14,15 Our work also demonstrates that many relationships between traditional risk factors and chronic diseases in the general population (e.g., obesity and hypertension) persist for HIV-infected patients. Furthermore, although much has been made of the contribution of antiretroviral therapy toward development of these conditions, our study indicates that the risk conferred by traditional factors is often comparable toand occasionally greater than-that due to antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Such conditions affected 13-48% of our subjects, rates similar to those published from other studies of HIV-infected patients. 3,14,15 Our work also demonstrates that many relationships between traditional risk factors and chronic diseases in the general population (e.g., obesity and hypertension) persist for HIV-infected patients. Furthermore, although much has been made of the contribution of antiretroviral therapy toward development of these conditions, our study indicates that the risk conferred by traditional factors is often comparable toand occasionally greater than-that due to antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 52%
“…Increased rates of dyslipidemia, cardiovascular disease, and diabetes are welldocumented, [1][2][3] with multiple factors (inflammation caused by HIV, antiretroviral effects, traditional risk factors, etc.) accounting for these findings.…”
Section: Introductionmentioning
confidence: 99%
“…LDL-C was calculated with the Friedwald's formula for TG < 4.5 mmol/l; non-HDL-C was 5 defined as (TC -HDL-C). ApoA1 and apoB were measured by immunonephelemetric method.…”
Section: -Initial Study Proceduresmentioning
confidence: 99%
“…However emergence of cardiovascular (CV) complications related to HIV infection per se and/or to c-ART has raised clinical and public health concerns [2][3][4][5] given the increasing duration of exposure to c-ART. Several classical CV risk factors including age, gender, body mass index (BMI), blood pressure, increased total cholesterol (TC) levels or tobacco consumption have been previously recognized in HIV+ patients 6 .…”
mentioning
confidence: 99%
“…Some studies have shown greater risk of cardiovascular events in persons with HIV/AIDS and on HAART as compared to those without treatment 21,22 . Among the antiretroviral drugs, the protease inhibitors 23 , lopinavir-ritonavir or indinavir 24 , and regimens containing abacavir or didanosine 25 show greater risk of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%